Structures and bonding of homoleptic bis(2,3-dihydro-1,3-diborole) complexes of nickel and platinum - Wadepohl, Hubert; Krüger, Carl; Siebert, Walter (Journal of organometallic chemistry, 2015)
Homoleptic metal complexes of the boron heterocycle 2,3-dihydro-1,3-diborole {(R1C)2(R2B)2R3(H)C} 1 are described. X-Ray crystal structure determinations of two nickel and platinum derivatives are presented. In the nickel complex [Ni(1d)2] 6d (R1 = R2 = R3 = Et) the essentially coplanar heterocycles attain a pentahapto coordination mode with a gauche orientation with respect to one another. An 18 VE count is attained. In contrast, in the 14 VE platinum complex [Pt(1a)2] 4a (R1 = R2 = Et, R3 = Me) the ligands are strongly folded and adopt a tetrahapto coordination. The molecule is centrosymmetric in the crystalline state. DFT MO calculations are presented to establish the relative stabilities of these coordination modes for nickel and platinum, respectively.
Gesehen am 26.06.2020